Days of adversity : the Warsaw uprising 1944 - McGilvray, Evan, 1961- (Helion & Company, 2016)
"This work is a re-examination of the decisions regarding the 1944 Warsaw Uprising made by the leadership of the underground Polish Army, as well as the questionable attitudes of senior Polish commanders in exile in London. The questions raised are, was the uprising necessary and why was it so poorly conducted by a totally indifferent leadership?"--Publisher.